Local government reform in Jamaica and Trinidad: a policy dilemma - Schoburgh, Eris D. (2007)
Issues of local governance have dominated Caribbean policy agenda for the past two decades, prompting considerable thought and action on local government reform by scholars, local government practitioners and policy makers, alike. No reforms have been as ubiquitous as those of local government. Permitted by an international reformist agenda, local government reform policy is linked positively to efforts to redress incapacities of public management and administration. This article examines conceptual and empirical issues relating to implementation of local government reform in two Caribbean countries, Jamaica and Trinidad. It analyses how the vision for local governance is articulated through specific reform taxonomies and argues that, although local government reform is normatively a policy aimed at fundamental changes in intergovernmental relations, in Jamaica and Trinidad reform has led merely to adjustments in the internal administration of local government. - Reproduced.
Keywords: Local government - Trinidad; Local government - Jamaica; Administrative reform - Trinidad; Administrative reform - Jamaica; Administrative reform